After orientalism : critical perspectives on western agency and eastern re-appropriations - Pouillon, Franc̦ois; Vatin, Jean-Claude (Leiden studies in Islam and society ;, 2015)
This book offers an exciting new landscape in which to situate research on cultures and societies of the non-European world, with a road-map that leads us beyond the restrictive dichotomy of Occident/Orient.